Early introduction of complementary food and childhood stunting were linked among children aged 6-23 months - Bunga Astria Paramashanti; Stella Benita (Jurnal Gizi Klinik Indonesia, 2020)
Background: Indonesia’s national stunting prevalence remains high. The transition from exclusive breastfeeding to poor complementary feeding practices may put infants at higher risk of becoming stunting. Objective: This study aimed to analyze the relationship between the early introduction of complementary food and stunting among young children aged 6-23 months in Kebumen Regency. Methods: A cross-sectional study design was conducted among 307 young children in Kebumen Regency, Central Java Province, Indonesia, by using multistage cluster sampling. Our primary outcome was stunting or height-for-age z-score <-2, whereas independent variables were child, maternal, and household factors. Univariate and multivariate logistic regression were performed to assess significant determinants at the level of significance 0.05. Results: Timely introduction of complementary food was a protective factor against stunting (AOR= 0.54; 95%CI: 0.31-0.94). Female children were less likely to be associated with stunting (AOR= 0.54; 95%CI: 0.32-0.93). Conversely, variables which significantly increased the risk of becoming stunting included older children aged 12-17 months (AOR= 2.01; 95%CI: 1.05-3.84) and 18-23 months (AOR= 4.17; 95%CI: 2.15-8.08) and maternal occupation in agricultural sectors (AOR= 3.77; 95%CI: 1.17-12.1). Conclusions: Child factors associated with stunting was the first timing of complementary feeding, child sex, and child age. The maternal factor linked to stunting was the mother's occupation in the agricultural sector. This study indicated that child and maternal factors play essential roles in childhood stunting.